Case Investigation on the Influence of In‐Snow Particles' Size and Composition on the Snow Light Absorption and Albedo - Xin Wang; Chunyu Zhang; Tenglong Shi; Daizhou Zhang; Pusheng Zhao; Peng Zhao (Geophysical Research Letters, 2023)
Abstract The snow physical parameters are closely related to the sizes, shapes, and chemical composition of light‐absorbing particles (LAPs). By utilizing a computer‐controlled scanning electron microscope software called IntelliSEM‐EPASTM, we first report the measured size‐resolved concentration of soot, dust, and fly ash particles in fresh (wet) and aged (dry deposition) snow samples collected at an industrial city in China during and after a snowfall at intervals of 6–8 days. Due to wet scavenging by seasonal snow, soot and dust particles in snow are absorbed by 69.7% and 30.3% at wavelengths of 550 nm, lowering snow albedo by 0.0089 and 0.0039, respectively. Soot particle size increases slightly during dry deposition, whereas size‐resolved mineral dust does not undergo a significant shift in particle size. These results indicate the essentiality to involve the effects of accurate size and composition of in‐snow LAPs for a better assessment of snow light absorption and reflectance.